Analisis Faktor-faktor yang Mempengaruhi Kualitas Pengelolaan Barang Milik Daerah pada Organisasi Perangkat Daerah (OPD) di Lingkungan Pemerintah Kabupaten Ogan Komering Ulu - Edwinsyah, Edwinsyah; Munajat, Munajat; Kenamon, Mardiah; Sari, Yunita (Universitas Batanghari Jambi, 2025)
This research aims to analyze the factors that influence the quality of management of regional property. The research uses quantitative descriptive methods using multiple linear regression to critically analyze factors that are thought to influence the quality of management of regional property within the Ogan Komering Ulu (OKU) Regency government environment. The results of this research show that simultaneously and partially the variables of apparatus quality, regulatory compliance and management information systems have a positive effect on the quality of management of regional property in the regional government of Ogan Komering Ulu Regency.